Prevalence of Overall and Abdominal Obesity among Adolescent High School Girls in Tabriz, Iran - Rafraf, Maryam (IIUM Medical Journal Malaysia, 2013)
Introduction: Obesity is a growing public health problem in both developed and developing societies. The aim of this cross-sectional study was to estimate the prevalence of overall obesity determined by body mass index (BMI) and abdominal obesity identified by waist circumference(WC) percentiles, waist to hip ratio(WHR) and waist to height ratio (WHtR), in adolescent girls attending high school in Tabriz, Iran. Methods: A sample of 985 girls was selected by stepwise random sampling from five districts of Tabriz. Weight, height, WC and hip circumferences ( HiC) of the subjects were measured and BMI, WHR and WHtR were calculated. Overweight and obesity were defined according to International BMI Cut-Off Points for adolescents. WC >90th percentile, WHR>0.80 and WHtR≥0.50 were categorized as abdominal obesity. Results: The prevalence rates of obesity and overweight were 2.8% and 16.4%, respectively. Abdominal obesity defined by WC percentiles, WHR, and WHtR were seen in 3.2%, 4.0%, and 18.2% of subjects, respectively. WHtR determined the highest prevalence of abdominal obesity in subjects compared to WC and WHR. WC, WHR, and WHtR were significantly related to BMI. Conclusions: Overall obesity and abdominal obesity are substantially prevalent in the studied adolescent girls. Further studies are needed to identify risk factors for the obesity in our studied population. Findings emphasize the importance of establishing community–based interventions in order to prevent the development of adolescent obesity and its complications in adulthood.